Nato@75 – the future of the Atlantic Alliance in tumultuous times - Rademacher, Fritz (Sodobni vojaški izzivi, 2024)
This article takes an in-depth look at the Atlantic Alliance as it is approaching its 75th anniversary. It analyses the prevalent strategic environment in which NATO operates, with its multiple risks and rivalries; and addresses the main elements on its agenda as it manages the numerous challenges to Euro-Atlantic security and defence of today and tomorrow. To this end, it offers insights into NATO’s main efforts in such areas as deterrence and defence, Ukraine, partnership, enlargement, transatlantic relations, resilience, upholding and protecting the international rules-based order, emerging and disruptive technologies, and climate change and security.
Keywords: mednarodni odnosi; NATO; obrambna politika; Rusija; varnost; vojaška politika; zavezništvo